New technologies and social control: contemporary legal challenges (Revista do Tribunal Regional Federal da 3ª Região, 2021)
Law, as an instrument for regulating life, usually keeps pace with reality, despite the fact that some defend its transformative nature, especially in Brazil - by virtue of our Constitution. This article will present some aspects and applications of the so-called new technologies with regard to social control, both in the private sphere and by state agents, as well as the resulting tensions. The inexorable tension between legal certainty, the limitation of freedom and the transformative nature of the law will be debated, with the aim of considering how the law and society can and/or should position themselves in the face of such challenges, based on the current social context and legal system, especially by virtue of fundamental rights.
Keywords: Social control; Legal certainty; Limitation of freedom; Social transformation; Digital technology; Profiling